Innovation Management of Islamic Religious Education Learning Models in Pesantren-Based Schools - Komarudin Komarudin; Ujang Nurjaman; Ahmad Sukandar; Ahmad Khori (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to describe the learning model of Islamic Religious Education in Islamic boarding schools and reveal its implications for learning Islamic religious education in public schools. The approach of the research is qualitative, and descriptive-analytical is the method. The data in this study were obtained through 1) Observation, 2). Interviews, 3) documentation. The results of this study indicate that this research has implications for three things: developing the concept of learning Islamic Religious Education in public schools, developing the implementation of learning Islamic Religious Education in public schools and developing an evaluation system for learning Islamic Religious Education in public schools. Then the implementation consists of learning in the classroom, habituation inside and outside the classroom and Islamic conditioning life in the school environment.